If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.75(8n + -12) + n = 5(n + 2) Reorder the terms: 0.75(-12 + 8n) + n = 5(n + 2) (-12 * 0.75 + 8n * 0.75) + n = 5(n + 2) (-9 + 6n) + n = 5(n + 2) Combine like terms: 6n + n = 7n -9 + 7n = 5(n + 2) Reorder the terms: -9 + 7n = 5(2 + n) -9 + 7n = (2 * 5 + n * 5) -9 + 7n = (10 + 5n) Solving -9 + 7n = 10 + 5n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-5n' to each side of the equation. -9 + 7n + -5n = 10 + 5n + -5n Combine like terms: 7n + -5n = 2n -9 + 2n = 10 + 5n + -5n Combine like terms: 5n + -5n = 0 -9 + 2n = 10 + 0 -9 + 2n = 10 Add '9' to each side of the equation. -9 + 9 + 2n = 10 + 9 Combine like terms: -9 + 9 = 0 0 + 2n = 10 + 9 2n = 10 + 9 Combine like terms: 10 + 9 = 19 2n = 19 Divide each side by '2'. n = 9.5 Simplifying n = 9.5
| 2n+4=3(4-2) | | -3-6=18 | | 1.5=1.5-0.12t | | 5+8m=-18 | | 3x+12-5x=24 | | 4x-4=-2-3-1 | | 0.02(x+4)=0.03x-0.02 | | 3m+7m-5=25 | | 3x+2=19+x | | x-8y=-26 | | -x-7+6x+10=-7 | | 14x=14x+18 | | 3sqrt(x^2+12)+5=9 | | 4n+2=-2(n+2) | | 3x+2.5=17.5 | | 16x^2-9y^2=729 | | 4r=-11 | | ln(x+1)+ln(x-1)=6 | | -2(1x+8)+3=5 | | 2-4(x+2)=4 | | 4=-14a+19b | | 2(-3n+5)=-4(n+4) | | 5-(2x-6)=5x+8 | | 8f+2+9=3f-f+29 | | 12+k*8=84 | | -52=4(5+6x) | | 142=x^2+8x | | 26=2(8+x) | | 10ab-6ab= | | 7(-7+4x)=118 | | 7(6+x)=6(x-3) | | -3(2n-3)=4(5-n) |